EXPLORING PREGNANT TOURISM: A PHENOMENOLOGICAL STUDY OF WOMEN’S LIVED EXPERIENCES IN SABANG - Eka Octavian Pranata; Nabila Fadhilah; Yulia Intan Fatriana; Aqilah Hilmi (Journal of Economics and Development, 2026)
This study is a qualitative research employing a phenomenological approach aimed at understanding the lived experiences of pregnant women engaging in tourism activities in Sabang, Indonesia. The focus of this study is to explore the subjective meanings constructed by pregnant tourists during their travel experiences. The informants consisted of 10 participants selected purposively based on their direct experience of traveling while pregnant. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis, including coding, categorization, and the development of essential meanings. The findings identify five major themes: risk perception and safety considerations, emotional dynamics, physical challenges, the role of support systems, and the meaning of travel during pregnancy. The results indicate that the tourism experiences of pregnant women are multidimensional, influenced by physical, psychological, social, and destination-related factors. This study contributes to the development of tourism studies, particularly in the area of pregnant tourism, and provides practical implications for developing more inclusive, safe, and pregnancy- friendly tourism environments.